EVALUATION OF THE INTERNAL CONTROL SYSTEM IN IMPROVING THE HEALTH SERVICE SYSTEM AT IBNU SINA HOSPITAL MAKASSAR - Tenriwaru Tenriwaru; Fadlia Nasaruddin (JOSAR (Journal of Students Academic Research), 2017)
This study aims to determine the application of the COSO internal control system in improving the health service system applicable to Ibnu Sina Hospital in Makassar. This research uses descriptive research with a qualitative approach. The data analysis method used is descriptive method with data collection, data reduction, descriptive data presentation and conclusion. The result of this research is that the internal control system at Ibnu Sina Hospital has been running quite well, which has implemented the existing internal control elements. Such as separation of duties, authorization system, using a computerized system in processing data. The health service system at Ibnu Sina Hospital is equipped with a good internal control system; the health service system has implemented elements of an effective internal control system.